Structural organization of the English cooking recipes dating back to the second half of the 19th century - L.R. Saetgaraeva; G.Kh. Gilazetdinova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The compositional characteristics of the English cooking recipes dating back to the second half of the 19th century were analyzed in detail using the Book of Household Management compiled by Isabella Mary Beeton (also known as Mrs Beeton), a famous Englishwoman, and published in 1861. Owing to the growing interest in the gastronomic discourse, this research is of particular relevance – although the language of cooking is rich, its specifics and evolution have been still understudied. It was found that the soup recipes from the book under consideration have such structural elements as titles, ingredients list, main bodies, and, in some cases, optional elements. All of these elements were described. A classification of the obligatory and optional elements was introduced. All recipe parts (in accordance with P.P. Burkova’s classification) were divided into introductory (title, list of ingredients), instructive (recipe body), and concluding blocks (time and money required for cooking, seasonality of ingredients, number of portions, information about the history of a particular ingredient). It was concluded that the structure of the English cooking recipes of the second half of the 19th century is stereotyped, which can be explained by the author’s ambition to make it easy for young and unskilled housewives to master the art of culinary and housekeeping.